Anatomical and tree rings differences in two provenances of Cordia trichotoma (Vell.) Arráb. ex Steud. (Boraginaceae) - Longui, Eduardo Luiz; Caum, Caroline [UNESP]; Tomazello-Filho, Mario; Lisi, Claudio Sergio; Roig, Fidel Alejandro; Marcati, Carmen Regina [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2022)
The parental effect on wood anatomy and growth rings of Cordia trichotoma trees was studied. Tree seeds of two provenances (Cerrado and Atlantic Forest biomes) were collected in 1986. Seedlings were planted, and after 25 years, twelve wood disks were collected from six trees from each provenance. Anatomical features and growth rings were analyzed according to standard techniques. Qualitative anatomy of wood indicated similarities between the two provenances, except for the presence of geniculate vessels found in woods from the Cerrado. However, the greatest differences in wood anatomy were quantitative. Provenances from Cerrado had wood with shorter vessel and fibers elements, less fiber lumen, less parenchyma per mm2, and more vessels per group than did provenances from the Atlantic Forest. Cross dating among the radial growth ring series was performed through visual and statistical procedures. The relationships between tree rings and meteorological records were performed through Pearson's correlation, and through dendro-climatic analysis that identified the end summer precipitation as the major factor affecting tree growth at inter annual timescale. The standard chronologies of tree-ring width series showed similarity between Cerrado and Atlantic Forest provenances, but with small differences in the juvenile period of live of trees. The rains that decreased between April and June associated with the gradual decrease in temperature may have reduced the cambial activity and caused the formation of tree rings with small differences between the two provenances. The results of this study are relevant for climate adaptive forestry: they emphasize the importance of heritability in the plasticity of certain features of wood anatomy related to the environmental conditions in which they grow, while the growth rate and its year-by-year variability show small differences.
Diferenças anatômicas e nos anéis de crescimento em árvores de duas procedências de Cordia trichotoma (Vell.) Arráb. ex Steud. (Boraginaceae)
Keywords: Heritability; Louro-pardo; Rainfall; Temperature; Wood features